Development and Evaluation of a Direct Sandwich Enzyme-Linked Immunosorbent Assay for the Quantification of Guinea-Pig Immunoglobulin E - Nishimura Makoto; Funaoka Hiroyuki; Hosoe Hiroaki; Ohkaru Yasuhiko; Yakuo Ikuhisa; Hayakawa Shinobu; Ito Koji (Elsevier, 2006)
Abstract.: The purpose of this study was to develop and evaluate a direct sandwich enzyme-linked immunosorbent assay (ELISA) for the immunoglobulin E (IgE) in serum and plasma from guinea pig using mouse monoclonal antibodies specific for guinea-pig IgE. Mouse monoclonal antibodies were raised against purified IgE protein. The ELISA was performed using a combination of two anti-IgE monoclonal antibodies. One antibody was labeled with horseradish peroxidase (HRP), and the other was coated on polystyrene wells. Purified guinea-pig IgE was used as the standard material. The validity of the ELISA was confirmed by precision, dilution, recovery, and interference tests. The range of detection was 3.1 - 800 ng of IgE mass per mL of serum and plasma. The intra- and inter-assay coefficients of variation were 4.6% and 5.7%, respectively, or less. The recovery test showed variation only between 92.1% and 111.8%, and the anticoagulants showed noninterference with the IgE assay. The mean serum IgE mass concentration in OVA-sensitized guinea pigs was 29438 ng/mL, and it was 48.6 ng/mL in normal guinea pigs. The present ELISA is useful and practical for specific measurement of the guinea-pig IgE, and it is surmised that it would be suitable for use in allergological and pharmacological research. Keywords:: Immunoglobulin E, sandwich enzyme-linked immunosorbent assay, monoclonal antibody, quantification